(untitled) (Asian Journal of Social Science Studies, 2022)
In today‟s world, countries are increasingly interconnected and their interdependence is obviously growing. Migration has taken on a distinctly contemporary character as people move more frequently. The current global migration patterns not only have some beneficial effects on nation states, but also poses new challenges to them. For example, developing countries are losing their talent. The structure of international illegal immigration is more complex and its identity is increasingly ambiguous. International migration, especially irregular migration, poses security challenges (territorial, public and cultural) to nation states. However, the study has found that the impact of international migration on security is both objective and subjective.